Millions on the Move the Aftermath of Partition - Ministry of Information and Broadcasting (Ministry of Information and Broadcasting, 1947)
Exactly a year before the transfer of power took place, there began with the Great Calcutta Killing of August 16, 1946, the sorry tale of mass murder and arson which was to be followed by the tragic events of Noakhali and Bihar. One disaster followed another, each producing a reaction in a different part of the country. The Frontier Province boiled up and Rawalpindi became for some months the worst affected area in the country.
Ministry of Information and Broadcasting
Ministry of Information and Broadcasting